2018
DOI: 10.1016/j.neuropharm.2018.09.018
|View full text |Cite
|
Sign up to set email alerts
|

Hippocampal NPY Y2 receptors modulate memory depending on emotional valence and time

Abstract: Posttraumatic stress disorder is characterized by contextually inappropriate, dys-regulated and generalized fear expression and often resistant to therapy. The hippocampus integrates contextual information into spatial and emotional memories, but how diverse modulatory neurotransmitters are shaping this process is not known. Neuropeptide Y is a peptide-neurotransmitter, which modulates hippocampal excitability by activating several G-protein-coupled receptors. Postsynaptic Y1 receptors create strong anxiolytic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
20
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 22 publications
(23 citation statements)
references
References 49 publications
2
20
1
Order By: Relevance
“…No previous studies have examined potential effects on memory after vector-mediated Y2 overexpression in normal rodents. However, re-expression of Y2 receptors in the dorsal hippocampus of Y2 knockout mice decreased spatial memory in mice (Hörmer et al, 2018). The present study using an AAV vector (CG01) with a CAG promotor to induce overexpression of both Y2 and NPY in septal and temporal hippocampus was not associated with a significant effect on short-term or long-term memory using the hippocampus-dependent Morris water maze test.…”
Section: Discussioncontrasting
confidence: 50%
See 1 more Smart Citation
“…No previous studies have examined potential effects on memory after vector-mediated Y2 overexpression in normal rodents. However, re-expression of Y2 receptors in the dorsal hippocampus of Y2 knockout mice decreased spatial memory in mice (Hörmer et al, 2018). The present study using an AAV vector (CG01) with a CAG promotor to induce overexpression of both Y2 and NPY in septal and temporal hippocampus was not associated with a significant effect on short-term or long-term memory using the hippocampus-dependent Morris water maze test.…”
Section: Discussioncontrasting
confidence: 50%
“…Central administration of NPY is known to have both inhibitory and stimulatory effects on memory, depending on the brain region, dose, memory test, and application time point in the learning process (for review see Gøtzsche and Woldbye, 2016). Experiments with Y2 receptor knockout mice and Y2 receptor antagonist indicate that Y2 receptors play an important role in mediating hippocampal memory-related effects of NPY (Redrobe et al, 2004;Gonçalves et al, 2012;Hörmer et al, 2018). Studies with AAV vectors encoding NPY have shown that hippocampal NPY overexpression may attenuate the memory-related synaptic phenomenon long-term potentiation (LTP) in vitro (Sørensen et al, 2008a,b).…”
Section: Discussionmentioning
confidence: 99%
“…In particular, Y1Rs seem to suppress fear learning in multiple brain areas, including the amygdala and hippocampus (Gutman et al, 2008 ; Lach and De Lima, 2013 ). On the other hand, activation of Y2Rs also inhibits acquisition and promotes extinction of fear memories (Verma et al, 2012 ), predominantly in the extended amygdala and hippocampus (Verma et al, 2015 , 2018a , b ; Tasan et al, 2016 ; Hormer et al, 2018 ). For example, local re-expression of hippocampal Y2Rs in Y2KO mice resulted in specific suppression of fear, by reducing fear recall and promoting fear extinction (Hormer et al, 2018 ).…”
Section: Introductionmentioning
confidence: 99%
“…The underlying mechanisms are still elusive, but a memory‐modulating effect may be one potential contributing factor. Along this line, a recent study demonstrated that hippocampal Y2Rs reduced the expression of contextual fear and re‐established impaired fear extinction . A concomitant reduction of spatial memory suggests that NPY may reduce fear by a general interference with memory consolidation.…”
Section: Neuropeptide Ymentioning
confidence: 89%